Toward an Archetypal Psychology of Disability Based on the Hephaestus Myth - Ebenstein, William (Disability Studies Quarterly, 2006)
Over the last 20 years disability scholars have analyzed representations of people with disabilities as they appear in literature, myth, art, film, media, and other cultural artifacts. This research can contribute to the development of a new archetypal psychology of disability. Archetypal psychology uses mythical and poetic modes of discourse to deepen our understanding of lived experience and behavior. The stories associated with the Greek god Hephaestus are among the earliest representations of disability. His image is pervasive and spans the Western imagination from the ancient Greeks to the present. Thus, a detailed study of this myth is a logical starting point. Archetypal images from different historical eras, and disciplines, co-exist in what C.G. Jung called the "collective unconscious" where they can be compared and contrasted with each other. The Hephaestus myth helps to organize many shared images of disability into meaningful patterns that can inform our understanding of disability in contemporary culture.